AGILE GOVERNANCE DALAM PELAYANAN PENEMPATAN DAN PERLINDUNGAN PMI, UPT P2TK DISNAKERTRANS JATIM - Silvia Jihan Rosyidah; Diana Hertati (Halu Oleo University, 2025)
The purpose of this study is to be able to identify, describe, and analyse the application of agile governance in PMI services, especially in placement and protection services for Indonesian Migrant Workers. The research method uses descriptive qualitative methods through interviews, documentation, and observation. Data sources use primary data and secondary data. The results of the study show that UPT P2TK has transformed from conventional services to revolutionary services.